ANALISIS NILAI KEADILAN RESTORATIF PADA PENERAPAN HUKUM ADAT DI INDONESIA - Tsurayya Istiqamah, Destri (Veritas et Justitia, 2018)
Already in 2014, restorative justice as a distinct approach within the general criminal justice system had been used as the basis to treat child victims and offenders (the child protection Act of 2014).  Nonetheless it is worth noticing that long before the promulgation of this Act, restorative justice has been used and is embedded in the living law of the Indonesian indigenous populations. This paper, using a descriptive analytical method, shall elaborate upon those traditional values found in the living law of the indigenous populations which resembles or reflects a restorative justice approach. In addition the author argues that this approach should also be used outside the limited scope of children criminal justice system.